CHEMICAL COMPOSITION OF PEAR FRUIT AND ITS IMPORTANCE FOR HUMAN HEALTH - X.M. Noibjonova; O.Z. Qayumjonov; M.M. Qayumjonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This study investigates the chemical composition of pear (Pyrus communis L.), particularly the Nashvati cultivar grown in Uzbekistan, with a focus on its macro- and microelement content and their significance for human health. Advanced analytical techniques, specifically inductively coupled plasma optical emission spectrometry (ICP-OES), were employed to determine the quantitative distribution of mineral elements in the fruit. The results revealed that potassium, phosphorus, calcium, and magnesium are present in relatively high concentrations, while trace elements such as iron, zinc, copper, and manganese were also detected in smaller amounts. The high phosphorus content highlights its essential role in bone formation, energy metabolism, and genetic processes.